Skincare consumption behavior: Study of beauty discourse and consumerism among Gen-Z women of Javanese ethnicity - Amalia, Anindita Firda (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
A significant surge of interest in skincare occurred due to growing awareness of maintaining skin health and beauty. This indicates a change in skincare as a necessity which contains complexity behind it. This study aims to unveil the involvement of various elements that produce and continuously encourage consumerism lifestyles among Javanese Gen-Z women using Herbert Marcuse's theory of one-dimensional man, alongside the concept of beauty discourse. This study uses qualitative methods with a phenomenological approach. This study shows that the development of consumerism lifestyle is influenced by the entire experience in consuming skincare. This includes the internalization of beauty discourse, the existence of financial strategies in the consumption process until the establishment of repressive tolerance which determines consumers’ integration into the capitalist’s repressively established system. Therefore, the degree of consumerism lifestyle determines consumers into certain dimensions, such as one-dimensional, semi-one-dimensional, and multi-dimensional consumers which gradually indicates a lower consumerism lifestyle.